THE EFFECT OF SELF-CONFIDENCE, SELF-EFFICACY, SCHOOL ENVIRONMENT, AND PARENTAL ATTENTION ON THE LEARNING ACHIEVEMENT OF 10TH GRADE STUDENTS THROUGH LEARNING MOTIVATION AS AN INTERVENING VARIABLE IN ECONOMICS AT MAN 1 PASAMAN - Candra, Andika; Desi Areva; Rika Verawati (Global Action and Education for Society, 2025)
This study aims to analyze: 1) the effect of self-confidence on learning motivation, 2) the effect of self-efficacy on learning motivation, 3) the effect of the school environment on learning motivation, 4) the effect of parental attention on learning motivation, 5) the effect of self-confidence on learning achievement, 6) the effect of self-efficacy on learning achievement, 7) the effect of the school environment on learning achievement, 8) the effect of parental attention on learning achievement, 9) the effect of learning motivation on learning achievement.This research is associative in nature. The population in this study consisted of 104 tenth-grade economics students at MAN 1 Pasaman in the 2024/2025 academic year. The sample consisted of 65 people using stratified random sampling. The research instrument used for this study was a closed questionnaire using path analysis and hypothesis testing with a t-test.The results of this study indicate that: 1) there is an effect of self-confidence on learning motivation, as shown by a path coefficient of 0.351 with a t-value of 4.812 > t-table 1.66864; 2) there is no effect of self-efficacy on learning motivation, as shown by a path coefficient of 0.167 with a t-value of 2. 147 < t-table 1.66864, 3) there is an effect of school environment on learning motivation, as indicated by a path coefficient of 0.321 with a t-value of 3.325 > t-table 1.66864, 4) There is an influence of parental attention on learning motivation, as indicated by a path coefficient of 0.195 with a t-value of 2.509 > t-table 1.66864. 5) There is a negative influence of self-confidence on learning achievement, as indicated by a path coefficient of -0.205 with a t-value of -5.441 < t-table 1.66864, 6) There is no effect of self-efficacy on learning achievement, as indicated by a path coefficient of -0.188 with a t-value of -4.365 < t-table 1.66864, 7) there is an influence of the school environment on academic achievement, as indicated by a path coefficient of 0.272 with a t-value of 6.411 > t-table 1.66864, 8) there is an influence of parental attention on academic achievement, as indicated by a path coefficient of 0.083 with a t-value of 2.116 > t-table 1.66864, 9) There is a negative influence of learning motivation on academic achievement, as indicated by a path coefficient of -0.217 with a t-value of 9.711 and a t-table value of 1.66864.